2023
DOI: 10.1002/acn3.51936
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variability associated with intronic FGF14 GAA repeat expansion in Japan

Masahiro Ando,
Yujiro Higuchi,
Junhui Yuan
et al.

Abstract: Background and ObjectivesThe GAA repeat expansion within the fibroblast growth factor 14 (FGF14) gene has been found to be associated with late‐onset cerebellar ataxia. This study aimed to investigate the genetic causes of cerebellar ataxia in patients in Japan.MethodsWe collected a case series of 940 index patients who presented with chronic cerebellar ataxia and remained genetically undiagnosed after our preliminary genetic screening. To investigate the FGF14 repeat locus, we employed an integrated diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The frequency of pathogenic expansions found in our ataxia cohort, considering the previously established threshold of 250 repeats, was remarkably high (23%), equivalent to or even higher than previous reports 6,7,1921,25,3436 . The difference in incidence is possibly linked to the population studied but it could also result from the sensitivity of the genetic test used.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The frequency of pathogenic expansions found in our ataxia cohort, considering the previously established threshold of 250 repeats, was remarkably high (23%), equivalent to or even higher than previous reports 6,7,1921,25,3436 . The difference in incidence is possibly linked to the population studied but it could also result from the sensitivity of the genetic test used.…”
Section: Discussionsupporting
confidence: 65%
“…Of note, the patient with later onset of Parkinsonism and dementia previously had tentative clinical diagnosis of multiple system atrophy, cerebellar subtype (MSA-C). This would be the third patient with this diagnosis in whom a FGF14 pathogenic expansion is identified 19,21 . However, in the context of our patient, a careful retrospective examination ruled out the MSA-C diagnosis and revealed that this patient in fact had a typical SCA27B phenotype with later onset of second diagnoses that are frequent in elderly people.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Future studies are needed to define the regional prevalence of SCA27B, although ongoing screening efforts suggest that SCA27B is also a relatively common cause of late‐onset ataxia in South Asia (10%) 21 and Brazil (9%) 43 . However, SCA27B may not be as common in East Asian populations, as it was not identified in 312 patients with suspected spinocerebellar degeneration of unknown cause from the Hokkaido island in northern Japan in one study 44 and was identified in only 11 of 940 individuals (1.2%) from Japan with chronic progressive cerebellar ataxia in another study 45 …”
Section: Epidemiology and Regional Distributionmentioning
confidence: 98%
“…43 However, SCA27B may not be as common in East Asian populations, as it was not identified in 312 patients with suspected spinocerebellar degeneration of unknown cause from the Hokkaido island in northern Japan in one study 44 and was identified in only 11 of 940 individuals (1.2%) from Japan with chronic progressive cerebellar ataxia in another study. 45 In Quebec, a frequency of SCA27B as high as 60% has been reported among French-Canadian patients with previously unexplained adult-onset ataxia, making it the most common genetic cause of adult-onset ataxia in this population. 21,46 The observation of a common disease haplotype shared by some French-Canadian patients suggest that the high proportion of SCA27B in this population may correspond to a founder effect in this population known to be enriched for such effects.…”
Section: Epidemiology and Regional Distributionmentioning
confidence: 99%